Silica nanocomposite-based fused silica lens and its processing

CN122916408APending Publication Date: 2026-10-16NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510433943.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,模具复制过程中压力梯度、不均匀的温度以及填充性不足等问题共同影响着复制结构的形状精度,尤其是在加工复杂微结构时其影响更为显著

Benefits of technology

[0028] The beneficial effects of this invention are as follows: This invention enables the efficient and high-precision machining of complex fused silica optical lenses by performing diamond turning and subsequent heat treatment on a silica nanocomposite material with excellent machinability. Compared to fused silica, the prepared silica nanocomposite material exhibits superior machinability, effectively avoiding the problems of severe tool wear and low machining efficiency encountered when directly machining fused silica. It can achieve damage-free optical surfaces under a wide range of process parameters, and various complex structures can be generated through ultra-precision turning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916408A_ABST
    Figure CN122916408A_ABST
Patent Text Reader

Abstract

The application discloses a fused quartz lens based on a silicon dioxide nanocomposite and a processing technology thereof, which comprises three steps of preparation of the silicon dioxide nanocomposite, super-precision diamond turning and high-temperature heat treatment. Firstly, nano silicon dioxide particles are mixed with a polymer to prepare the silicon dioxide nanocomposite with excellent mechanical properties; then, super-precision turning forming of a complex optical surface is completed by using single-point diamond turning; finally, degreasing and sintering treatment are carried out in a muffle furnace to obtain a transparent and dense fused quartz optical lens with a complex shape. The method utilizes excellent cutting performance of the silicon dioxide nanocomposite, effectively avoids various problems of direct cutting of the fused quartz, and combines flexibility and high efficiency of turning processing, so that rapid design and manufacture of complex fused quartz optical elements can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of precision machining technology for optical components, specifically to a fused silica lens based on silica nanocomposite materials and its machining process. Background Technology

[0002] Fused silica, with its superior mechanical properties, light transmission, chemical resistance, and thermal stability, is an ideal material for manufacturing optical lenses and has wide applications in the optical field. However, these very properties also present challenges to the fabrication of complex fused silica optical lenses. Currently, grinding and polishing are the main methods for processing fused silica optical lenses; however, due to limitations in the shape and size of polishing tools, they are primarily used for processing lenses with simple rotational symmetry shapes, such as aspherical lenses. Furthermore, the grinding and polishing process can easily cause subsurface damage to the lens, thereby reducing its performance.

[0003] To address the challenges of machining fused silica, methods such as glass molding, laser-assisted turning, and energy field-based etching have been proposed for forming complex fused silica lenses. Glass molding can achieve the formation of complex glass lenses at the micrometer to millimeter scale; however, the high temperatures required for fused silica molding (approximately 1300°C) limit the available mold materials. Currently, materials with extremely high hardness, such as glassy carbon and tungsten carbide, are mainly used as molds for fused silica molding. Their difficult-to-machining characteristics and the maintenance issues of the molds directly increase the cost of forming complex fused silica optical lenses. Laser softening of fused silica allows for turning, but only surface roughness at the tens of nanometer level can be achieved, and the cutting tools suffer significant wear after prolonged turning. Chemical etching and ion beam etching can form complex microstructures on the surface of fused silica; however, their etching mechanisms are complex, and the shape accuracy of the structure is difficult to control effectively.

[0004] To address the difficulties associated with directly processing fused silica, processing methods based on silica nanocomposites, which have gradually developed in recent years, promise to become a reliable means of creating complex fused silica optical components. Currently, there are two main approaches to indirectly process and shape complex fused silica optical components using silica nanocomposites. The first approach utilizes additive manufacturing, based on the principle of photopolymerization, employing photopolymerization 3D printing technologies such as digital light processing, two-photon polymerization, and tomographic reconstruction to form complex-shaped silica nanocomposites. Subsequent debinding and high-temperature sintering then transform them into transparent and dense fused silica. These technologies can be used to process complex fused silica optical lenses such as aspherical surfaces, lens arrays, and diffractive elements. However, these 3D printing technologies struggle to balance printing accuracy and efficiency, and the stress generated during photopolymerization can cause additional deformation in the printed parts. The second approach uses mold replication to shape silica nanocomposites, followed by heat treatment to transform them into fused silica. Methods include injection molding, hot pressing, and casting. This approach offers higher processing efficiency and is suitable for mass production. However, issues such as pressure gradients, uneven temperatures, and insufficient filling during mold replication collectively affect the shape accuracy of the replicated structure, especially when processing complex microstructures. Furthermore, the processing, wear, and maintenance of the molds make this approach unsuitable for the rapid design and manufacturing of complex structures, while also increasing processing costs. In conclusion, there is currently a lack of an efficient and high-precision method for processing complex fused silica optical components. Summary of the Invention

[0005] The purpose of this invention is to address the difficulties in processing complex fused silica optical elements by providing a high-efficiency, high-precision fused silica lens based on silica nanocomposite materials and its processing technology, which improves the efficiency and precision of lens processing while ensuring the surface roughness of the lens.

[0006] The technical solution adopted in this invention is:

[0007] A processing method for fused silica lenses based on silica nanocomposite materials includes the following steps:

[0008] Step 1: Preparation of silica nanocomposite materials;

[0009] Step 2: Perform high-precision turning on a machine tool on the silica nanocomposite material;

[0010] Step 3: The processed silica nanocomposite material is placed in a muffle furnace for heat treatment to transform it into a transparent and dense fused silica lens.

[0011] Further, step 1 specifically includes:

[0012] The polymer, solvent, and crosslinking agent are mixed and stirred to obtain component A. While stirring, silica nanoparticles are added in batches, and stirring is continued to obtain component B. Finally, a photoinitiator is added and stirring is continued to obtain nanoparticle slurry C. Nanoparticle slurry C is injected into a transparent silicone mold and photocured by ultraviolet light to obtain bulk silica nanocomposite material. Finally, thermal cycling is performed in a forced-air drying oven to remove residual stress caused by photocuring.

[0013] Furthermore, the silica nanoparticles used are Aerosil OX50, with an average particle size of 40 nm and a purity of ≥99.8%.

[0014] Furthermore, in component A, the mass ratio of polymer, solvent, and crosslinking agent is 68:25:7; in component B, the mass percentage of silica nanoparticles is 50%; and in slurry C, the mass percentage of photoinitiator is 0.5%.

[0015] Furthermore, the polymer is hydroxyethyl methacrylate, the solvent is phenoxyethanol, the crosslinking agent is tetraethylene glycol diacrylate, and the photoinitiator is diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide.

[0016] Furthermore, the wavelength of the ultraviolet light used during curing is 405nm, and the ultraviolet irradiation time is 3min.

[0017] Furthermore, the silica nanocomposite material underwent 10 thermal cycles in a forced-air drying oven at a rate of 5℃ / min between 50℃ and 110℃.

[0018] Furthermore, step 2 specifically includes:

[0019] The solidified bulk silica nanocomposite material is adhered to the end face of a copper rod, which has been pre-machined flat and fixed in a collet fixture. The fixture is then fixed to the machine tool spindle using vacuum adsorption. Finally, ultra-precision turning is used to complete the cutting of the complex surface. The silica nanocomposite material rotates with the spindle C and moves along the X-axis, while the tool reciprocates along the Z-axis. The combined motion of the three axes constitutes a spatial Archimedean spiral tool trajectory in the corresponding cylindrical coordinate system. The calculation process of the tool trajectory is as follows: In the two-dimensional plane, the sampling angle ns and feed rate f are defined in the spiral tool trajectory. Then, the relative spatial position of the nth tool and the machined surface in the tool trajectory, i.e., the tool position point, can be represented by the spindle angular position θ(n) and radial position ρ(n):

[0020] θ(n) = ns + θ(n-1), θ(1) = 0

[0021]

[0022] Let the surface shape being processed be represented by z. s =S(ρ,θ), where the tool position is the distance between the tool and z. s When tangent, assuming the tool is located at a certain distance above the machined surface, the relative position of the tool in space is expressed as: Its projection on the machined surface is represented as When the tool moves with the minimum projected distance and contacts the machined surface, at which point the tool is tangent to the machined surface, the distance the tool moves along the Z-axis is:

[0023]

[0024] Finally, a tool path containing the spindle position (θ), X-axis position (ρ), and Z-axis position is obtained, and the silica nanocomposite material is turned with ultra-precision according to the calculated tool path.

[0025] Furthermore, step 3 specifically includes:

[0026] The silica nanocomposite material was sintered in an air atmosphere in a muffle furnace. First, it was heated to 600℃ at a heating rate of 0.33℃ / min to complete the debinding, with holding periods of 2h at 150℃, 400℃, and 600℃ respectively. Then, it was heated to 1250℃ at a heating rate of 2℃ / min and held at 1250℃ for 30min to complete the sintering. Finally, it was cooled to room temperature at a cooling rate of 3℃ / min to obtain a transparent and dense fused silica lens.

[0027] A fused silica lens based on silica nanocomposite material, wherein the fused silica lens is processed using the above-described process.

[0028] The beneficial effects of this invention are as follows: This invention enables the efficient and high-precision machining of complex fused silica optical lenses by performing diamond turning and subsequent heat treatment on a silica nanocomposite material with excellent machinability. Compared to fused silica, the prepared silica nanocomposite material exhibits superior machinability, effectively avoiding the problems of severe tool wear and low machining efficiency encountered when directly machining fused silica. It can achieve damage-free optical surfaces under a wide range of process parameters, and various complex structures can be generated through ultra-precision turning.

[0029] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The invention will now be described in further detail with reference to the figures. Attached Figure Description

[0030] Figure 1 This is a schematic diagram of the preparation process of silica nanocomposite materials.

[0031] Figure 2 This is a schematic diagram of the ultra-precision turning process.

[0032] Figure 3 This is a schematic diagram of the tool path calculation process. Detailed Implementation

[0033] The specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0034] The processing technology for fused silica lenses based on silica nanocomposite materials of this invention includes three steps: preparation of silica nanocomposite materials, ultra-precision turning, and heat treatment. The preparation process of the silica nanocomposite materials is as follows: Figure 1 As shown, silica nanoparticles, polymer, solvent, crosslinking agent, and photoinitiator are thoroughly stirred using mechanical stirring to obtain a silica nanoparticle slurry. This slurry is then poured into a transparent silicone mold and cured using ultraviolet light to obtain a silica nanocomposite material. Specifically, the silica nanoparticles used are Aerosil OX50 with an average particle size of 40 nm and a purity ≥99.8%; the polymer is hydroxyethyl methacrylate; the solvent is phenoxyethanol; the crosslinking agent is tetraethylene glycol diacrylate; and the photoinitiator is diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide. When preparing the slurry, the polymer, solvent, and crosslinking agent are first mixed and thoroughly stirred to obtain component A. While stirring, silica nanoparticles are added in batches to obtain component B. After the addition of silica nanoparticles is complete, the photoinitiator is added, and stirring continues for 30 minutes to finally obtain a photocurable slurry C. Specifically, the mass ratio of polymer, solvent, and crosslinking agent in component A is 68:25:7; the mass percentage of silica nanoparticles in component B is 50%-55%; and the mass percentage of photoinitiator in the final slurry C is 0.05%. Slurry C is then injected into a transparent silicone mold and cured by irradiation with a parallel ultraviolet light source with a wavelength of 405nm and a power of 15W for 3 minutes to obtain a blocky silica nanocomposite material. The obtained silica nanocomposite material is placed in a forced-air drying oven and repeatedly heated and cooled 10 times within the temperature range of 50℃-100℃ at a rate of 5℃ / min to remove residual stress caused during the photocuring process.

[0035] The ultra-precision turning process of silica nanocomposites is as follows: Figure 2As shown, the cured blocky silica nanocomposite material is adhered to the end face of a copper rod using paraffin wax. The end face of the copper rod has been pre-machined flat and fixed in a collet fixture. The fixture is then fixed to the machine tool spindle using vacuum adsorption. Finally, ultra-precision turning is used to complete the cutting of complex surfaces. The silica nanocomposite material rotates with the spindle C and moves along the X-axis, while the tool reciprocates along the Z-axis. The combined motion of these three axes constitutes a spatial Archimedean spiral tool trajectory in a cylindrical coordinate system, enabling the turning of any complex surface. The calculation process of the tool trajectory is as follows... Figure 3 As shown, in a two-dimensional plane, the sampling angle ns (°) and feed rate f (mm / rev) are defined in a helical tool path. Then, the relative spatial position of the nth tool and the machined surface in the tool path, i.e., the tool position point, can be represented by the spindle's angular position θ (n) and radial position ρ (n) as follows:

[0036] θ(n)=ns+θ(n-1),θ(1)=0#(1)

[0037]

[0038] Assume the surface shape being processed can be represented as z s =S(ρ,θ), the tool position point, i.e., the distance between the tool and z. s The position when they are tangent. For example... Figure 3 As shown, assuming the tool is located at a certain distance above the machined surface, it is necessary to calculate the distance the tool moves along the Z-axis to ensure that the tool is tangent to the machined surface. The relative position of the diamond tool in space can be expressed as... Its projection on the machined surface can be expressed as Therefore, when the tool moves with the minimum projected distance and contacts the machined surface, at which point the tool is tangent to the machined surface, the distance the tool moves along the Z-axis is:

[0039]

[0040] Finally, a tool path containing the spindle position (θ), X-axis position (ρ), and Z-axis position is obtained. Ultra-precision turning of the silica nanocomposite material is performed according to the calculated tool path. Due to the excellent mechanical properties of the silica nanocomposite material, the spindle speed can be freely adjusted within the range of 10 rpm to 2000 rpm, the depth of cut can be adjusted within the range of 2 μm to 10 μm, and the feed rate can be adjusted within the range of 2 μm / rev to 5 μm / rev, depending on the complexity of the surface shape.

[0041] After turning, the fixture was placed on a heating table, and paraffin wax was melted at 70°C. The structured silica nanocomposite material was removed and thoroughly cleaned with anhydrous ethanol. The cleaned silica nanocomposite material was then placed in a muffle furnace. First, the temperature was increased to 600°C at a heating rate of 0.33°C / min to complete degreasing, and then held at 150°C, 300°C, and 600°C for 2 hours. Then, the temperature was increased to 1250°C at a heating rate of 2°C / min and held at 1250°C for 30 minutes to complete sintering. Finally, the temperature was decreased to room temperature at a cooling rate of 3°C / min to obtain a transparent and dense fused silica optical lens.

[0042] The process principle of this invention mainly relies on the bonding effect of the polymer in the silica nanocomposite material and the low-temperature sintering driven by the high surface energy of the nanoparticles. The polymer used in this invention is hydroxyethyl methacrylate, whose molecular chain contains hydroxyl groups. The silica nanoparticles used are hydrophilic Aerosil OX50. Therefore, the silica nanoparticles exhibit excellent dispersibility in the polymer, and the silica particles can be interconnected through the polymer, thus ensuring the uniformity of the nanocomposite material. During photopolymerization, the polymer and crosslinking agent undergo a photopolymerization reaction and crosslink with each other, thereby transforming the composite material from a liquid slurry to a solid mass, enhancing the bonding force between silica particles and between silica particles and the polymer. After photopolymerization, the polymer acts as a binder, bonding the nanoparticles into a predetermined arbitrary shape and providing sufficient mechanical strength to maintain its structure. Therefore, the final silica nanocomposite material possesses excellent mechanical properties, enabling it to be machined to achieve optical surface shaping. Furthermore, the silica nanoparticles used in this invention have an average particle size of 40 nm, and their extremely small size gives them a very high specific area and surface energy. Based on the Gibbs-Thomson effect, the silica nanoparticles used in this invention have a lower melting point than fused silica due to their extremely small size. This allows for densification between particles at a relatively low temperature (approximately 1250°C) through mechanisms such as surface diffusion and viscous flow. This effectively avoids the high temperature of approximately 1700°C required in the traditional fused silica preparation process, thereby effectively reducing energy consumption and equipment requirements.

[0043] The present invention will now be compared with two existing preparation methods:

[0044] First, compared to the commonly used grinding and polishing processes for fused silica optical lenses, the process route proposed in this invention offers greater flexibility and efficiency. Currently, grinding and polishing technologies are mature and can achieve extremely high surface quality and shape accuracy in fused silica optical lenses. However, due to the extremely high hardness of fused silica, grinding and polishing can introduce subsurface damage, such as microcracks or stress layers, thus affecting the optical performance and long-term use of the lens. Furthermore, the processing requires multiple abrasive changes, making the steps cumbersome, especially for high-precision lenses, which may require even more steps, thus reducing production efficiency. Simultaneously, due to the excellent mechanical strength of fused silica, its material removal rate is low; typically, the removal amount over several hours is only a few micrometers. This also reduces the processing efficiency of large-size fused silica lenses and makes the process unsuitable for mass production. In addition, due to the limitations of polishing tool size, this process is basically only applicable to the processing of simple rotationally symmetric lenses, such as spherical lenses and aspherical lenses, and is difficult to process complex-shaped lenses such as microlens arrays and diffractive lenses. In contrast, the process proposed in this invention utilizes the presence of polymers in the silica nanocomposite material, resulting in a hardness far lower than fused silica. This makes it extremely easy to machine into any complex shape through turning. By changing the cutting tools of different radii, it is possible to achieve rapid and high-precision machining of large-diameter spherical and aspherical lenses, as well as complex-shaped lenses such as microlens arrays, freeform surfaces, and diffraction elements. Simultaneously, the excellent machinability of the silica nanocomposite material effectively reduces subsurface damage caused by turning.

[0045] Secondly, compared with laser-assisted fused silica turning, the process route proposed in this invention has lower costs, higher processing efficiency, and effectively reduces tool wear during processing. Laser-assisted turning focuses a laser at the tool tip to soften the fused silica in the cutting area, thus enabling the turning of fused silica. However, laser-assisted systems are expensive and energy-intensive, increasing the overall processing cost. Under laser irradiation, localized thermal stress in the material may lead to microcracks or thermal damage, thereby reducing lens performance. Furthermore, although the fused silica is softened by the laser during cutting, the cutting depth is still relatively low, currently only reaching about 1 μm, and the tool still wears after prolonged turning. In contrast, the silica nanocomposite material in this invention can achieve a cutting depth of tens of micrometers, effectively improving processing efficiency. Moreover, due to the presence of the polymer, tool wear is extremely low, significantly reducing tool consumption and saving costs.

[0046] This invention, by controlling the ratio of silica to polymer in a silica nanocomposite material, obtains a composite material with excellent mechanical and machinability. Complex optical lenses can be rapidly and precisely machined using conventional turning processes, and subsequently transformed into transparent and dense fused silica optical lenses through high-temperature heat treatment. These lenses possess mechanical and optical properties comparable to commercially available fused silica. This invention effectively avoids the shortcomings of current processes for directly machining fused silica, broadens the pathways for processing fused silica optical lenses, and increases the flexibility of fused silica optical lens manufacturing.

[0047] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A processing technology for fused silica lenses based on silica nanocomposite materials, characterized in that, Includes the following steps: Step 1: Preparation of silica nanocomposite materials; Step 2: Perform high-precision turning on a machine tool on the silica nanocomposite material; Step 3: The processed silica nanocomposite material is placed in a muffle furnace for heat treatment to transform it into a transparent and dense fused silica lens.

2. The processing technology for fused silica lenses based on silica nanocomposite materials according to claim 1, characterized in that, Step 1 specifically involves: The polymer, solvent, and crosslinking agent are mixed and stirred to obtain component A. While stirring, silica nanoparticles are added in batches, and stirring is continued to obtain component B. Finally, a photoinitiator is added and stirring is continued to obtain nanoparticle slurry C. Nanoparticle slurry C is injected into a transparent silicone mold and photocured by ultraviolet light to obtain bulk silica nanocomposite material. Finally, thermal cycling is performed in a forced-air drying oven to remove residual stress caused by photocuring.

3. The processing technology for fused silica lenses based on silica nanocomposite materials according to claim 2, characterized in that, The silica nanoparticles used were Aerosil OX50, with an average particle size of 40 nm and a purity of ≥99.8%.

4. The processing technology for fused silica lenses based on silica nanocomposite materials according to claim 3, characterized in that, In component A, the mass ratio of polymer, solvent and crosslinking agent is 68:25:7; in component B, the mass percentage of silica nanoparticles is 50%; and in slurry C, the mass percentage of photoinitiator is 0.5%.

5. The processing technology for fused silica lenses based on silica nanocomposite materials according to claim 3, characterized in that, The polymer is hydroxyethyl methacrylate, the solvent is phenoxyethanol, the crosslinking agent is tetraethylene glycol diacrylate, and the photoinitiator is diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide.

6. The processing technology for fused silica lenses based on silica nanocomposite materials according to claim 3, characterized in that, The wavelength of the ultraviolet light used during curing was 405nm, and the ultraviolet irradiation time was 3min.

7. The processing technology for fused silica lenses based on silica nanocomposite materials according to claim 3, characterized in that, The silica nanocomposite material underwent 10 thermal cycles at a rate of 5℃ / min between 50℃ and 110℃ in a forced-air drying oven.

8. The processing technology for fused silica lenses based on silica nanocomposite materials according to any one of claims 3-7, characterized in that, Step 2 specifically involves: The solidified bulk silica nanocomposite material is adhered to the end face of a copper rod, which has been pre-machined flat and fixed in a collet fixture. The fixture is then fixed to the machine tool spindle using vacuum adsorption. Finally, ultra-precision turning is used to complete the cutting of the complex surface. The silica nanocomposite material rotates with the spindle C and moves along the X-axis, while the tool reciprocates along the Z-axis. The combined motion of the three axes constitutes a spatial Archimedean spiral tool trajectory in the corresponding cylindrical coordinate system. The calculation process of the tool trajectory is as follows: In the two-dimensional plane, the sampling angle ns and feed rate f are defined in the spiral tool trajectory. Then, the relative spatial position of the nth tool and the machined surface in the tool trajectory, i.e., the tool position point, is represented by the spindle angular position θ(n) and radial position ρ(n): θ(n) = ns + θ(n-1), θ(1) = 0 Let the surface shape being processed be represented by z. s =S(ρ,θ), where the tool position is the distance between the tool and z. s When tangent, assuming the tool is located at a certain distance above the machined surface, the relative position of the tool in space is expressed as: Its projection on the machined surface is represented as When the tool moves with the minimum projected distance and contacts the machined surface, at which point the tool is tangent to the machined surface, the distance the tool moves along the Z-axis is: Finally, a tool path containing the spindle position (θ), X-axis position (ρ), and Z-axis position is obtained, and the silica nanocomposite material is turned with ultra-precision according to the calculated tool path.

9. The processing technology for fused silica lenses based on silica nanocomposite materials according to claim 8, characterized in that, Step 3 specifically involves: The silica nanocomposite material was sintered in an air atmosphere in a muffle furnace. First, it was heated to 600℃ at a heating rate of 0.33℃ / min to complete the debinding, with holding periods of 2h at 150℃, 400℃, and 600℃ respectively. Then, it was heated to 1250℃ at a heating rate of 2℃ / min and held at 1250℃ for 30min to complete the sintering. Finally, it was cooled to room temperature at a cooling rate of 3℃ / min to obtain a transparent and dense fused silica lens.

10. A fused silica lens based on silica nanocomposite material, characterized in that, The fused silica lens is obtained by the process described in any one of claims 3-9.